Amperometric Trace Determination of V(V) and Cr(VI) with Enthanethioic Acid - Khatkar, S.P.; Bala, Vinod (Asian Journal of Chemistry, 2010)
Ethanethioic acid (thioaceticacid, ETA) has been employed for the amperometric determination of V(V) in 0.1 M KCI and Cr(VI) in acetate buffer medium of pH 4.99 at d.m.e. While Cr(VI) method involves no chemical interaction and is based on the phenomenon of mutual compensation of cathodic current of metal species and anodic current of ETA, V(V) method seems to be the consequence of complexation reaction. Metal species-ETA titrimetric ratio has been found to be 1 : 2 for V(V) and 1 : 3.32 for Cr(VI). Solutions as dilute as 5.09 ppm [(V(V)] and 0.52 ppm Cr(VI) have been estimated with high degree of accuracy. Tolerance limits for foreign ions have also been worked out.